Assessing Travellers’ Perceptions For Achieving Sustainable Transportation: A Case Study In Klang Valley. - Jen, Sim Ho; Lee, Vien Leong; Mohd Sadullah, Ahmad Farhan (2009)

(untitled)
In Malaysia, alleviating traffic congestion in major cities has always been given the top priority. Despite various remedial measures and efforts to improve public transport in Kuala Lumpur, there are nearly 2.2 million private vehicles moving into the city centre daily.